Project-based learning as an approach to enhance ecological component in professional education - Tetiana M. Derkach; Mariia M. Bilianska; Olga G. Yaroshenko (Academy of Cognitive and Natural Sciences, 2023)
93 undergraduate and graduate students of the Kyiv National University of Technologies and Design were interviewed to assess students' attitudes to using upcycling technologies and changes in this attitude over the years of study. Students receive professional education in the clothing industry, studying technology, design, and vocational education and training. Despite the generally positive attitude, studies have shown a lack of understanding of the benefits arising from the application of waste administration technologies. Both junior and senior students demonstrated similar bimodal distributions concerning perceived benefits. Approximately half of the students (sceptics) disagree with the benefits, and the other half (optimists) express barely noticeable confidence in the benefits. The changes to the curricula of two disciplines for one of the specialities (vocational education and training) included several classes on problem-based and project-based learning and preparation and execution of ecology-related projects. This experiment changed the existing preferences of students significantly, reducing to zero the number of sceptics and forming a one-peak Gaussian of optimists. Understanding the main problems of waste management is essential in enhancing the ecological component of training future clothing industry specialists operating under sustainable development conditions.